Creating planning margins and imaging intervals for intracranial stereotactic radiosurgery treatment using patient log files. (24th May 2018) - Agnew, A; Jordan, K; Strbac, B; Galal, M M
Abstract: To account for intra-fractional patient movement during stereotactic radiosurgery, Cyberknife utilises two orthogonal ceiling mounted kV sources that can be used to track patient movement with a variable imaging interval of between 15 and 150 s according to the user's discretion. Imaging intervals can be optimised to keep imaging dose to a minimum while retaining delivery accuracy. Log files recorded during the treatment delivery can be used to establish both optimum imaging interval and also a suitable treatment margin to account for the patient movement that cannot be accounted for by imaging. Log files for 56 intracranial patients (100 fractions, 5000 image pairs) were retrospectively assessed for patient movement. Movement between consecutive images was investigated, along with the movement of the patient over the duration of the treatment. It was found that from image to image, patient movement did not vary with respect to interval times. The standard deviation (SD) for the movement between images was found to be 0.32, 0.36 and 0.33 mm for superior/inferior (SI), left/right (LR) and anterior/posterior (AP) movement respectively. The rate of drift between the images was used to calculate that an interval of 28 s was required to restrict the translational movement of the patient to 0.1 mm for 95% of the population. As no relationship could be found between the interval times and movement, it cannot be assumed that the patient movement between images is linear. This movement cannot be accounted for by additional imaging but could be accounted for using additional planning margins. This work shows that log files that have been verified can be used to create treatment margins and imaging intervals. To ensure target coverage, a 0.8 mm margin (0.7 for stochastic and 0.1 for systematic) is recommended, and an imaging interval of 30 s.